Analisis Yuridis terhadap Kasus Pencemaran Nama Baik melalui Media Sosial: Studi Kasus Tuduhan 'Mafia BBM' terhadap AM - Fisensius Samara; Yoseph Gerard Dangga; Alifiyah Khairani Habshari; Andreas Juliano Pedi Radja; Joseano Tedy Petrov Palla; Claudius Siku; Jhon Wesley Malaikosa (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research analyzes the legal implications and proof of defamation crimes committed through social media platforms, especially TikTok, within the context of Article 310 paragraph (1) of the Indonesian Criminal Code (KUHP). The case studied involves the alleged defamation against Algajali Munandar, who was publicly accused of being a